Validation of the Psychometric Properties of the Conflict Resolution Styles Inventory in the University Population - Andrés Ramírez; Venus Medina-Maldonado; Luis Burgos-Benavides; Alhena L. Alfaro-Urquiola; Hugo Sinchi; Javier Herrero Díez; Fco. Javier Rodríguez-Diaz (Social Sciences)
This study aimed to validate the psychometric properties of the Conflict Resolution Styles Inventory (CRSI) within the context of the university population in Ecuador. The CRSI measures how individuals manage interpersonal conflicts, a critical skill for university students. A sample of 746 university students from various institutions across Ecuador participated in the study. The CRSI, which categorizes conflict resolution styles into five types (competing, avoiding, accommodating, collaborating, and compromising), was translated and culturally adapted for the Ecuadorian context. Psychometric analyses, including factor analysis and reliability testing, were conducted to assess the validity and reliability of the inventory. The factor analysis supported the five-factor structure of the CRSI, confirming that the inventory is suitable for measuring distinct conflict resolution styles in this population. The inventory showed good internal consistency, with Cronbach’s alpha values exceeding 0.70 for all subscales. Additionally, the test–retest reliability indicated stability over time. The validated CRSI provides a robust instrument for understanding and improving conflict resolution skills among university students in Ecuador, contributing to better interpersonal relationships and academic environments.